Indigenous rights in the age of the UN declaration - Pulitano, Elvira, 1970- (Cambridge : Cambridge University Press, 2012)
'This examination of the role played by the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) in advancing indigenous peoples' self-determination comes at a time when the quintessential Eurocentric nature of international law has been significantly challenged by the increasing participation of indigenous peoples on the international legal scene. Even though the language of human rights discourse has historically contributed to delegitimise indigenous peoples' rights to their lands and cultures, this same language is now upheld by indigenous peoples in their on-going struggles against the assimilation and eradication of their cultures. By demanding that the human rights and freedoms contained in various UN human rights instruments be now extended to indigenous peoples and communities, indigenous peoples are playing a key role in making international law more'humanising' and less subject to State priorities.'--pub. desc.
Indigenous rights and international law : an introduction / Elvira Pulitano -- Indigenous self-determination, culture, and land : a reassessment in light of the 2007 UN Declaration on the Rights of Indigenous Peoples / Siegfried Wiessner -- Treaties, peoplehood, and self-determination : understanding the language of indigenous rights / Isabelle Schulte-Tenckhoff -- Talking up indigenous peoples' original intent in a space dominated by state interventions / Irene Watson and Sharon Venne -- Australia's Northern Territory intervention and indigenous rights on language, education and culture : an ethnocidal solution to Aboriginal'dysfunction'? / Sheila Collingwood-Whittick -- Articulating indigenous statehood : Cherokee state formation and implications for the UN Declaration on the Rights of Indigenous Peoples / Clint Carroll -- The freedom to pass and repass : can the UN Declaration on the Rights of Indigenous Peoples keep the US-Canadian border ten feet above our heads? / Carrie E. Garrow -- Traditional responsibility and spiritual relatives : protection of indigenous rights to land and sacred places / Kathleen J. Martin -- Seeking the corn mother : transnational indigenous organizing and food sovereignty in native North American literature / Joni Adamson -- 'Use and control' : issues of repatriation and redress in American Indian literature / Lee Schweninger -- Contested ground : aina, identity, and nationhood in Hawaii / Ku'ualoha Ho'omanawanui -- Kanawai, international law, and the discourse of indigenous justice : some reflections on the Peoples' International Tribunal in Hawaii / Elvira Pulitano -- Afterword. Implementing the Declaration / Mililani B. Trask.
Includes bibliographical references and index.
Keywords: United Nations. -- General Assembly; Indigenous peoples -- Civil rights; Indigenous peoples -- Legal status, laws, etc; Indigenous peoples (International law)